Malaria: Factors affecting disease severity, immune evasion mechanisms, and reversal of immune inhibition to enhance vaccine efficacy. - Xin-Zhuan Su; Fangzheng Xu; Rachel V Stadler; Awet Alem Teklemichael; Jian Wu (PLoS Pathogens)
Malaria is a complex parasitic disease caused by species of Plasmodium parasites. Infection with the parasites can lead to a spectrum of symptoms and disease severity, influenced by various parasite, host, and environmental factors. There have been some successes in developing vaccines against the disease recently, but the vaccine efficacies require improvement. Some issues associated with the difficulties in developing a sterile vaccine include high antigenic diversity, switching expression of the immune targets, and inhibition of immune pathways. Current vaccine research focuses on identifying conserved and protective epitopes, developing multivalent vaccines (including the whole parasite), and using more powerful adjuvants. However, overcoming the systematic immune inhibition and immune cell dysfunction/exhaustion may be required before high titers of protective antibodies can be achieved. Increased expression of surface molecules such as CD86 and MHC II on antigen-presenting cells and blocking immune checkpoint pathways (interactions of PD-1 and PD-L1; CTLA-4 and CD80) using small molecules could be a promising approach for enhancing vaccine efficacy. This assay reviews the factors affecting the disease severity, the genetics of host-parasite interaction, immune evasion mechanisms, and approaches potentially to improve host immune response for vaccine development.